Significant decisions of the Supreme Court, 1975-76 term - Fein, Bruce E. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1977)
This is the seventh volume in the American Enterprise Institute$1 (Bs continuing series of annual reviews of major Supreme Court decisions. It contains concise summaries of all the major opinions rendered by the Court during the October 1975 term, plus analysis of the development of the law in a number of fields, such as criminal law and procedure, the federal system, First Amendment rights, and government regulation. Highlights also include developments on the death penalty and on campaign financing and descriptions of the justices$1 (Bpositions on the role of courts and the judiciary in American society.s
Includes bibliographical references and index.
lje 24/01/2019
Loans
Keywords: Constitutional law; Supreme court; United States